Investigation of the Performance of Bituminous Binder Modified with Calcium Carbonate and Polyethylene Compound - Erkus, Yunus; Kok, Baha Vural; Yilmaz, Mehmet (Asce-Amer Soc Civil Engineers, 2022)
In this study, the usability of calcium carbonate-polyethylene compound (PEC) was investigated as an alternative to styrene-butadiene-styrene (SBS), which is one of the most used additives in bitumen modification. The softening point, penetration, rotational viscosity, bending beam rheometer, dynamic shear rheometer, multiple stress creep recovery, and fourier transform infrared spectroscopy tests were applied to the bituminous binders. To reveal the effectiveness of PEC modification, the PEC and SBS modified binders were compared in terms of performance and cost. As a result, with the use of PEC in bitumen, penetration decreased, whereas softening point, viscosity, and rutting parameters increased. PEC also improved the low-temperature performance of pure bitumen. PEC modification offered low-stress sensitivity and made the binder suitable for heavy traffic conditions. When all experiments were evaluated together, it was determined that 9% PEC modification gave similar or better results than 4% SBS modification in terms of performance and cost. Consequently, it was revealed that PEC can be used as a good alternative to SBS in bitumen modification.
Keywords: Bitumen modification; Calcium carbonate and polyethylene compound (PEC); Styrene-butadiene-styrene (SBS); Cost; Rheological properties